Seismic Response of Liquid Storage Tanks on Base Isolated Structures With Triple Friction Pendulum System - NUH, HAMZA HASSAN (İstanbul Kültür Üniversitesi, 2022)
The use of base isolation systems is a common and effective method of reducing the seismic response of structures. This thesis investigates the seismic response of liquid storage tanks in a base isolated structure isolated with Triple Friction Pendulum bearings subjected to six unidirectional near-field ground motions. The time history analysis of the structure was conducted with the Sap2000 structural analysis program. The seismic response of liquid storage tanks with different aspect ratios located in different floors was investigated for both the fixed base and the isolated structure using the floor accelerations obtained from the time history analysis of the building model. Seismic response of the contained liquid has been modelled using a mechanical analogue model which considers the flexibility of the tank wall. The variation of tank design parameters namely, the base shear, overturning moment, and liquid sloshing displacement were investigated for the fixed base and isolated structure using a MATLAB script. The analysis results indicate that base isolation can significantly reduce the dynamic response of tanks during earthquake ground motion events, especially for the tanks located on the upper floors of the structure.
Sıvı Depolama Tanklarının Üçlü Sürtünmeli Pendulum Sistemi ile Taban İzoleli Yapılar Üzerindeki Sismik Tepkisi
▪ Yüksek lisans tezi.